Antarctica disclosing: the contribution of the Museo Nazionale dell’Antartide - Earth Science Section of Siena - Sandroni, Sonia; Palmeri, Rosaria; Zeoli, Antonio; Folco, Luigi; Ricci, Carlo Alberto (2012)
The Museo Nazionale dell’Antartide was established in 1996 and is comprehensive of three sections characterised by different scientific aims: biology and ecology (Genova section), Earth science (Siena section) and marine geology and Antarctic exploration (Trieste section). The Museum has the aim to preserve, study, and increase the value of all scientific materials collected during the Italian research expeditions in Antarctica, and to promote the knowledge of scientific results achieved by the Italian Antarctic research community. The Earth Science section of Siena is the national repository for the geological material (rocks, fossils and meteorites) collected during the Italian Antarctic expedition since 1985, and has the aim to acquire, preserve, manage, catalogue and classify all the collection samples. Since 1996, within the frame of national and international research projects, scientific researches are carried out at the Siena section by a large variety of researchers. Antarctic samples, since 1996 Principal collection-based studies include i) the geology and petrology of metamorphic basement rocks of the Ross Orogen, ii) the mineralogy and geochemistry of Antarctic meteorites, iii) the provenance analyses of glacimarine drill core sediments recovered in the Ross Sea, and iv) the ice-flow analogue modelling. Achieved scientific results are largely attested by the many publications on peerreviewed international journals (H-index of 17, Web of Knowledge database source), and by the participation to national and international conferences. The Earth science section is particularly devoted to promote the polar knowledge to as wide an audience as possible, with special attention dedicated to all-level students and educators, through guided visits, lectures and didactic laboratories. The presence at the Siena section of scientists directly involved within Antarctic researches allows the visitors to be updated with some of the currently more crucial scientific arguments, as the global warming and the origin of ...